The cryo-EM structure of a γ-TuSC elucidates architecture and regulation of minimal microtubule nucleation systems - Zupa, Erik (Nat Commun, 2020)
The nucleation of microtubules from αβ-tubulin subunits is mediated by γ-tubulin complexes, which vary in composition across organisms. Aiming to understand how de novo microtubule formation is achieved and regulated by a minimal microtubule nucleation system, we here determined the cryo-electron microscopy structure of the heterotetrameric γ-tubulin small complex (γ-TuSC) from C. albicans at near-atomic resolution. Compared to the vertebrate γ-tubulin ring complex (γ-TuRC), we observed a vastly remodeled interface between the SPC/GCP-γ-tubulin spokes, which stabilizes the complex and defines the γ-tubulin arrangement. The relative positioning of γ-tubulin subunits indicates that a conformational rearrangement of the complex is required for microtubule nucleation activity, which follows opposing directionality as predicted for the vertebrate γ-TuRC. Collectively, our data suggest that the assembly and regulation mechanisms of γ-tubulin complexes fundamentally differ between the microtubule nucleation systems in lower and higher eukaryotes.